Tuberculin reaction and BCG scar: association with infant mortality. Issue 12 (22nd October 2015) - Timmermann, Clara Amalie Gade; Biering‐Sørensen, Sofie; Aaby, Peter; Fisker, Ane Bærent; Monteiro, Ivan; Rodrigues, Amabelia; Benn, Christine Stabell; Ravn, Henrik
Abstract: Objective: To test the hypothesis that having a scar and a positive tuberculin skin test (TST) response after vaccination with Bacille Calmette–Guérin (BCG) is associated with reduced infant mortality. Methods: We studied cohorts of 2709 normal‐birthweight (NBW) and 1102 low‐birthweight (LBW) infants in Guinea‐Bissau. Children were enrolled in randomised trials between year 2002 and 2008 and received BCG vaccination at birth. BCG scars and TST responses were assessed at 2 and 6 months of age. The infants were followed for mortality to 12 months of age, and survival was analysed using Cox regression. Results: At age 2 months, 88% of NBW children and 91% of LBW children had a BCG scar, and 36% and 17% had a TST response, respectively. The LBW infants had nearly twofold higher mortality (4.5%) than the NBW infants (2.8%) between 2 and 12 months of age. In the LBW cohort, the adjusted mortality rate ratio (MRR) comparing children with a BCG scar with those without was 0.42 (95% CI = 0.19; 0.93). There was a similar tendency for TST positivity: MRR = 0.47 (95% CI = 0.14; 1.54). For LBW children who had both a positive TST reaction and a scar, the MRR was 0.22 (95% CI = 0.05; 0.87). For NBW children, a scar and a positive TST were associated with 20% reductions in mortality, which did not reach statistical significance. Conclusion: We confirmed previous observations that having a scar and a TST response after BCG vaccination is associated with lower mortality risk. The possibility of revaccinating scar‐negative children should be considered.